The characterisation of coals for combustion - Lester, Edward (1994)
The use of coal in the production of energy, will continue around the world into the next century, and onwards. From an environmental perspective, as well as a financial one, man has attempted to increase the efficiency of energy production from initial raw materials. Environmentally, the poor conversion of coal to energy means a waste of earth's resources, as well as the production of more waste. From a financial viewpoint, poor combustion means less energy per tonne of coal, hence less profit. Poor combustion will also mean higher levels of carbon in ash. Increased carbon levels will change the physical properties of the ash, and therefore reduce the possible number of outlets for its disposal.